Stepped impedance patch antenna for sub-6GHz 5G range - Hamza Becirspahic; Sehabeddin Taha Imeci (Heritage and Sustainable Development)
This article presents the design of a stepped impedance patch antenna for fifth generation mobile communication networks application. A large tendency towards the new generation is what drives this research. The antenna is designed and simulated in Sonnet Suites software. The overall dimensions of the antenna are 10.7x22.5 mm2. The antenna design is fed via a probe. The simulation is done in the range from 0 to 6GHz. The results achieved are compatible with 5th generation standards. The magnitude of input matching is -14.35dB and the maximum gain, at the radiating frequency of 4.82GHz, is found to be 5.045dB. The cross-polarization level is as low as -30dB. The goal of the research is achieved and presented in this paper.